PENERAPAN METODE DRILL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI HIMPUNAN KELAS VII PADA SUATU SMP DI SENTANI [THE IMPLEMENTATION OF THE DRILL METHOD TO INCREASE STUDENTS' COGNITIVE LEARNING OUTCOMES OF SETS IN A GRADE 7 CLASS AT A JUNIOR HIGH SCHOOL IN SENTANI] - Sari, Thresia Novita; Appulembang, Oce Datu (Universitas Pelita Harapan, 2019)
Learning outcomes are student’s responsibility after learning something. Furthermore, it is very important to achieve national education goals. This research is based on the students’ low cognitive learning outcomes. As evidenced by students’ scores, most of them have not been able to achieve the 60 KKM set in mathematics lessons and they lack practice and accuracy in doing mathematical problems. Because of students’ low cognitive learning outcomes, the researcher applied the drill method to overcome this problem and to understand how the implementation of the drill method increases students' cognitive learning outcomes. The research method used was Classroom Action Research (CAR) by Kemmis and McTaggart which was carried out from July to October 2017 in three cycles. The subjects were 21 students of grade 7C at A Junior High School in Sentani. The instruments used in this research were written test sheets, observation sheets, student questionnaires, and interview guidelines. To process the quantitative data, the researcher used descriptive statistical analysis while qualitative data used descriptive qualitative. Based on the results of the research, it can be concluded that the implementation of the drill method does improve students' cognitive learning outcomes in the set material with the percentage of students who reached the KKM in the first, second and third cycle being 52%, 71%, and 86% respectively. Besides implementing the drill method steps, this research also conducted the following: (1) reviewing the material, (2) giving motivation, (3) emphasizing important concepts, (4) checking students' understanding, (5) involving all students working on a variety of questions, (6) guiding students with difficulties, (7) correcting individual and classical mistakes, and (8) reminding students of time and thoroughness.BASAHA INDONESIA ABSTRACT: Hasil belajar merupakan tanggung jawab siswa setelah melakukan kegiatan pembelajaran. Selain itu, hasil belajar sangat penting dalam ketercapaian tujuan pendidikan nasional. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar kognitif siswa. Hal tersebut terlihat dari nilai-nilai yang diperoleh siswa, sebagian besar siswa belum mampu mencapai KKM 60 pada pelajaran Matematika, serta kurangnya latihan dan ketelitian siswa dalam mengerjakan soal-soal Matematika. Berdasarkan fakta rendahnya hasil belajar kognitif siswa, maka peneliti menerapkan metode drill untuk mengatasi masalah tersebut dan mengetahui penerapan metode drill dalam meningkatkan hasil belajar kognitif siswa. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan model Kemmis dan McTaggart yang dilaksanakan pada Juli sampai Oktober 2017 dalam tiga siklus. Subyek penelitian adalah 21 siswa kelas VII C pada suatu SMP di Sentani. Instrumen yang digunakan pada penelitian ini berupa lembar tes tertulis, lembar observasi, lembar angket siswa, dan pedoman wawancara. Pengolahan data kuantitatif pada penelitian ini menggunakan analisis statistik deskriptif sedangkan data kualitatif menggunakan deskriptif kualitatif. Berdasarkan hasil penelitian, disimpulkan bahwa penerapan metode drill dapat meningkatkan hasil belajar kognitif siswa pada materi himpunan dengan persentase siswa yang mencapai KKM pada siklus I, II dan III sebesar 52%, 71%, dan 86%. Selain melaksanakan langkah-langkah metode drill, pada penelitian ini juga dilakukan hal-hal sebagai berikut: (1) mereview materi, (2) memberikan motivasi, (3) menekankan konsep penting, (4) mengecek pemahaman siswa, (5) melibatkan seluruh siswa mengerjakan soal yang bervariasi, (6) membimbing siswa yang mengalami kesulitan, (7) memperbaiki kesalahan secara individual dan klasikal, serta (8) mengingatkan siswa tentang waktu dan ketelitian.